Challenges in the diagnosis and treatment of secondary acute myeloid leukemia. (June 2019) - Ossenkoppele, Gert; Montesinos, Pau
Graphical abstract: Highlights: sAML includes AML after cytotoxic, radiation, or immunosuppressive therapy (tAML). sAML also includes progression from a prior hematologic disorder. Outcomes of conventional chemotherapy (eg, 7 + 3) are typically poor in sAML patients. CPX-351 is approved for newly diagnosed tAML and AML-MRC. A good understanding of sAML and optimal treatment is important to improve outcomes. Abstract: Secondary AML (sAML), referring to AML arising after prior cytotoxic/radiation/immunosuppressive therapy (tAML) or an antecedent hematologic disorder, now primarily classified as AML with myelodysplasia-related changes (AML-MRC), accounts for 10%–30% of AML cases and is associated with a poor prognosis. sAML has historically been treated with intensive chemotherapy (eg, 7 + 3) or less aggressive regimens (eg, low-dose cytarabine or azacytidine for older/unfit patients); however, outcomes are typically poor, especially for older adults. Recently, CPX-351, a liposomal co-encapsulation of cytarabine and daunorubicin at a synergistic ratio, demonstrated improved front-line outcomes in older patients with high-risk/sAML. CPX-351 has been approved for adults with newly diagnosed tAML or AML-MRC and has an NCCN category 1 recommendation for induction therapy of patients aged >60 years with high-risk/sAML. Other novel therapies may also benefit certain sAML subgroups. Greater clarity around the optimal diagnosis and treatment of sAML patients is needed to improve outcomes in this high-risk subpopulation.